The Influence of Family Function Implementation on Teenagers’ Society in Jambi Province - Nofi Nurman; Betri Wendra; Afrin Khan (NALAR FIQH: Jurnal Hukum Islam, 2023)
Family functions consist of physical maintenance, socialization and education, acquisition of new family members through procreation or adoption. Control of social and sexual behavior, maintenance of family morals and maturation of family members through forming sexual partners and releasing adult family members. ¬ However, current conditions describe conditions that indicate that the role of the family in building and nurturing family members is increasingly weak. This study aims to determine whether there is a significant influence between the implementation of eight family functions on the social status of adolescents in Jambi province. This research is a quantitative study using SKAP 2018 secondary data (families and youth) so it is expected that the results of this study can be representative of the population studied. the level of vulnerability of adolescent association in Jambi Province shows the number 53.33. This means that most of the teenagers in Jambi Province are dating. Overall, the implementation of eight (8) family functions has no significant effect on the social status of adolescents.